Residue-Pole Methods for Variability Analysis of S-parameters of Microwave Devices with 3D FEM and Mesh Deformation - Rahimzadeh Rufuie, Mehrdad; Lamecki, Adam; Sypek, Piotr; Mrozowski, Michal (Společnost pro radioelektronické inženýrství, 2020)
This paper presents a new approach for variability analysis of microwave devices with a high dimension of uncertain parameters. The proposed technique is based on modeling an approximation of system by its poles and residues using several modeling methods, including ordinary kriging, Adaptive Polynomial Chaos (APCE), and Support Vector Machine Regression (SVM). The computational cost is compared with the traditional Monte-Carlo method. To improve the efficiency, mesh deformation is applied within 3D FEM framework.
Keywords: kriging; uncertainty quantification; surrogate models; microwave filters; vector fitting; mesh-morphing